Population-based screening for prostate cancer by measuring free and total serum prostate-specific antigen in Sweden. - Hugosson, J; Aus, G; Bergdahl, S; Fernlund, P; Frösing, R; Lodding, P; Pihl, C; Lilja, H (2003)
OBJECTIVE: To report the initial results from Sweden of a large population-based randomized study of screening using prostate-specific antigen (PSA) to detect prostate cancer, as the efficacy of such screening to decrease prostate cancer mortality has not yet been proven. METHODS: From the population registry men aged 50-66 years were randomized to screening (9973) and to future controls (9973). Men randomized to screening were invited to have their serum measured for free PSA (fPSA) and total PSA (tPSA) in serum using the Prostatus f/tPSA assay (Perkin-Elmer, Turku, Finland). Men with a tPSA of < 3.0 ng/mL were not further investigated, while those with a tPSA of > or = 3.0 ng/mL were investigated with a digital rectal examination (DRE), transrectal ultrasonography (TRUS) and sextant biopsies. RESULTS: Of those invited, 60% accepted PSA testing and 11.3% had a tPSA of > or = 3.0 ng/mL. Altogether 145 cancers were detected (positive predictive value, PPV, 24%); none were stage M1, two were stage N+ and 10 stage T3-4. Most (59%) cancers were impalpable and 39% were both impalpable and invisible on TRUS. At biopsy, 7% were Gleason score 2-4, 71% 5-6, 19% 7 and 2% Gleason score 8-10. A threshold tPSA of > or = 4.0 ng/mL would have detected 109 cancers in 366 biopsied men (PPV 30%) while cancer detection would have been 14% higher with a PPV of 36% using a threshold tPSA of > or = 3.0 ng/mL combined with a f/tPSA threshold of < or = 18%. CONCLUSIONS: PSA screening detects early-stage low-grade prostate cancer. Both the sensitivity and specificity can be increased by incorporating f/tPSA with a tPSA threshold of < 4 ng/mL.